FRI0403 Mitochondrial dysfunction and oxidative stress in myositis: a central pathogenic pathway from mouse to man. (12th June 2018) - Boyer, O.; Meyer, A.; Boitard, C.; Abad, C.
Abstract : Background: Myositides are severe diseases leading to a bedridden state and possibly death. The lack of animal model with spontaneously-occurring autoimmune myositis has hampered pathophysiological and therapeutic research. Autoimmune-prone NOD mice represent an invaluable model of type 1 diabetes (T1D). Inducible T cell co-stimulator (ICOS) is involved in germinal centre reaction and induction of helper T cell responses. We developed a unique model of myositis by invalidating the ICOS pathway in NOD mice 1 . Muscle holoproteome analysis in diseased mice together with observations of mitochondrial dysfunction in patients with dermatomyositis 2 suggest a main role of oxidative stress in disease pathogenesis. Objectives: To determine the pathogenic role of oxidative stress and evaluate the effect of antioxidant therapy on Icos -/- NOD myositis. Methods: Disease course was studied in Icos -/- NOD mice by grip strength, locomotor analysis and MRI. Muscle pathology was evaluated after conventional stainings, or by immuno-enzymology or immuno-histochemistry. Muscle-infiltrating cells were characterised by flow cytometry. New autoantibodies were identified in mice by serum proteomic analysis and sought for in myositis patients by ALBIA. Mouse muscle proteomic and transcriptomic analyses were performed by LC-MS/MS (Orbitrap) and RT-PCR, respectively. Muscle free radical production was assessed by EPR. Mice were treated by prednisolone (10 mg/kg/day) or N-acetylcysteine (2 g/L) in drinking water. Results: Icos -/- NOD mice did not develop diabetes. Instead, myositis spontaneously occurred with decreased grip strength, impaired cadence, reduced print area and death around 40 wks. Pathological muscle analysis revealed necrotic myofibers and important inflammatory infiltrates (CD4 + T cells, macrophages). Muscle lesions yielded MRI T2 hypersignals that regressed under steroids. CD4 + T cells transferred disease to NOD. scid recipients. Serum proteomic analysis revealed a new autoantibody directed against a mitochondrial antigen. It was found present in ~1% individuals from a~700 myositis patient cohort. Oxydative stress was manifest in Icos -/- NOD muscle by augmented free radical production, H2 O2 production-related atrophy, altered O2 consumption and dysregulation of several mitochondrial genes and proteins. N-acetylcysteine partially prevented myositis or ameliorated established disease. Conclusions: This work establishes Icos -/- NOD mice as a unique paradigm of myositis. A new autoantibody was discovered. Oxidative stress is present in diseased muscle. Antioxidant therapy is effective in a preventive or curative fashion. Together with our previous data in dermatomyositis patients 2, this work indicates the central role of mitochondrial dysfunction and oxidative stress in myositis pathogenesis and opens new perspectives for therapy. References: [1] Briet C, et al. The Spontaneous Autoimmune Neuromyopathy in ICOSL-/- NOD Mice Is CD4+ T-Cell and Interferon-γ Dependent. Front Immunol. 2017;8:287. [2] Meyer A, et al. IFN-β-induced reactive oxygen species and mitochondrial damage contribute to muscle impairment and inflammation maintenance in dermatomyositis. Acta Neuropathol2017;134:655. Acknowledgements: This work was supported by the Association Française contre les Myopathies, the European Union and Normandie Regional Council. Europe gets involved in Normandie with European Regional Development Fund (ERDF). Disclosure of Interest: O. Boyer Grant/research support from: CSL Behring, Celogos, Consultant for: CSL Behring, Inova Diagnostics, A. Meyer: None declared, C. Boitard: None declared, C. Abad: None declared